Hubungan Indeks Massa Tubuh (Imt) Dengan Usia Menarche Pada Siswi Sd Negeri Kota Pekanbaru - Mayasari, Sartika -; Hasanah, Oswati -; Hasneli, Yesi - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this study was to identify the correlation between body mass index (BMI) with age of menarche an Elementary school students in Pekanbaru  city. The design used was descriptive correlation with cross sectional, conducted on 374 elementary school girl. The sampling technique used  cluster sampling. The Results showed the average age of menarche was 11,86 years. The average of weight was 45,40 Kg. The average of  BMI has 20,09. The results used spearman correlations test showed there were  correlation a moderate correlation (r= -0,201)between BMI with age of menarche (p=0,000< α 0,05). This study suggested school institutions and parents to provide guidance and counseling about  nutrition and provide information about the right time to prepare the puberty and menarche on their adolessence girl. Keywords              : Body mass Index, Menarche